Developing an experimental basis for understanding transport in NIF hohlraum plasmas - Barrios, MA; Moody, JD; Suter, LJ; Sherlock, M; Chen, H; Farmer, W; Jaquez, J; Jones, O; Kauffman, RL; Kilkenny, JD; Kroll, J; Landen, OL; et al. (American Physical Society, 2018)
We report on the first multilocation electron temperature (Te) and flow measurements in an ignition hohlraum at the National Ignition Facility using the novel technique of mid-Z spectroscopic tracer “dots.” The measurements define a low resolution “map” of hohlraum plasma conditions and provide a basis for the first multilocation tests of particle and energy transport physics in a laser-driven x-ray cavity. The data set is consistent with classical heat flow near the capsule but reduced heat flow near the laser entrance hole. We evaluate the role of kinetic effects, self-generated magnetic fields, and instabilities in causing spatially dependent heat transport in the hohlraum.